2011
DOI: 10.1371/journal.pone.0021374
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Catalogue of the Euchromatic Male-Specific Region of the Horse Y Chromosome: Comparison with Human and Other Mammals

Abstract: Studies of the Y chromosome in primates, rodents and carnivores provide compelling evidence that the male specific region of Y (MSY) contains functional genes, many of which have specialized roles in spermatogenesis and male-fertility. Little similarity, however, has been found between the gene content and sequence of MSY in different species. This hinders the discovery of species-specific male fertility genes and limits our understanding about MSY evolution in mammals. Here, a detailed MSY gene catalogue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 88 publications
8
103
2
Order By: Relevance
“…Hence, the TSPY gene expression is more during early spermatogenesis process and as the spermatogenesis continued for several years after sexual maturity; its gene expression is reduced in subsequent ages. The decreased expression of USP9Y gene was in general, negatively correlated with semen volume, sperm concentration, initial sperm motility and post-thaw motility, which was not in agreement with earlier reports of Paria et al, (2011) and Mukherjee et al, (2013), who postulated that USP9Y gene was a single copy gene in cattle. In human, Vineeth and Malini (2011) observed that USP9Y gene could not be considered as a major gene involved in spermatogenesis.…”
Section: Testis Specific Protein On Y-encodedcontrasting
confidence: 93%
See 1 more Smart Citation
“…Hence, the TSPY gene expression is more during early spermatogenesis process and as the spermatogenesis continued for several years after sexual maturity; its gene expression is reduced in subsequent ages. The decreased expression of USP9Y gene was in general, negatively correlated with semen volume, sperm concentration, initial sperm motility and post-thaw motility, which was not in agreement with earlier reports of Paria et al, (2011) and Mukherjee et al, (2013), who postulated that USP9Y gene was a single copy gene in cattle. In human, Vineeth and Malini (2011) observed that USP9Y gene could not be considered as a major gene involved in spermatogenesis.…”
Section: Testis Specific Protein On Y-encodedcontrasting
confidence: 93%
“…However, in the present study DDX3Y gene has been used as a reference gene. This gene has been reported to be a single copy gene in the genome of mammals (Paria et al, 2011). Its utility has also been established in relative quantification in bulls and its expression level has been reported to remain unchanged irrespective of seasons and age (Yue et al, 2014).…”
Section: Selection Of Y-specific and Reference Genesmentioning
confidence: 99%
“…The male-specific primers of five Y chromosome genes -CUL4BY, ETSTY1, ETSTY4, ETSTY5, and SRYwere acquired from Paria et al (2011). Details of primers are shown in Table 2.…”
Section: Primer Designmentioning
confidence: 99%
“…Thus, it is crucial to make clear of its CNV for a better understanding of SRY gene in donkeys. The testisspecific transcript Y (ETSTY) family is identified to consist of equine-specific genes (Paria et al, 2011); three of them (ETSTY1, ETSTY4, and ETSTY5) were chosen to analyze the CNVs in this study. The copy number of the cullin 4 B Y (CUL4BY) gene has been detected in other species, such as cats and dogs (Murphy et al, 2006;Pearks Wilkerson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the horse this region was very helpful in mapping of the euchromatic region of the equine Y-chromosome. These investigations were very helpful for the prediction of male fertility in horses and are therefore considered in horse breeding [4,5].…”
Section: Genetics Of Eutherian Sex Determination and Dose Compensationmentioning
confidence: 99%